Genome organization: connecting the developmental origins of disease and genetic variation. (29th August 2017) - Jacobson, E.; Vickers, M. H.; Perry, J. K.; O'Sullivan, J. M.
Abstract : An adverse early life environment can increase the risk of metabolic and other disorders later in life. Genetic variation can modify an individual's susceptibility to these environmental challenges. These gene by environment interactions are important, but difficult, to dissect. The nucleus is the primary organelle where environmental responses impact directly on the genetic variants within the genome, resulting in changes to the biology of the genome and ultimately the phenotype. Understanding genome biology requires the integration of the linear DNA sequence, epigenetic modifications and nuclear proteins that are present within the nucleus. The interactions between these layers of information may be captured in the emergent spatial genome organization. As such genome organization represents a key research area for decoding the role of genetic variation in the Developmental Origins of Health and Disease.